p53 Protein: Master Regulator of Apoptosis and its Application in Cancer Therapy: p53 Protein: Master Regulator of Apoptosis and its Application in Cancer Therapy - Gohil, Chiragkumar J. (International Journal of Pharmaceutical & Biological Archive, 2019)
Cancer is characterized by uncontrolled and abnormal cells growth. In the body, the cell growth and cell division are governing by apoptosis. The process of apoptosis is mainly regulated by the p53 protein. p53 is a tumor suppressor protein. The amount of p53 in a cell is mainly controlled by the negative regulator murine double minute 2 (MDM2), which on complex formation with p53 leads to an overall reduction of the p53 level. Inhibition of p53 function will inhibit the apoptosis and leads to cancer. Consequently, inhibition of the MDM2/p53 interaction using the small molecules activates the p53 function and apoptosis in the cells which contain the wild-type p53. It is a promising new therapeutic strategy for the treatment of cancers retaining wild-type p53. However, the safety window of this class of compounds must be evaluated. Moreover, it has to require the development of compounds, which can also be able to target the cells which contain the mutated or deleted p53.